MENINGKATKAN KOMITMEN KARYAWAN MELALUI EMPLOYEE STOCK OWNERSHIP PROGRAM UNTUK MENINGKATKAN KESEJAHTERAAN KARYAWAN - Elizabeth Tiur Manurung (JRAK, 2018)
The purpose of this research is to ascertain the implementation of ESOP which has proven to increase employees’ commitment and motivation that can be measured through company’s profit proxy, and the increase in profit could increase employees’ welfare. This research used descriptive method that ensure each characteristic of the variables to obtain the validity of the data, hence it could be proven and improved to solve problems and create logical conclusion. PT Bandung has established stock fund through ESOP program, with the diversion partly of common stocks IDR 600 million on a par of 600.000 shares. The result of this research has proven a significant impact of implementation of ESOP, such as increasing in employee’s commitment and motivation. The 257,7% increase in profit compare to last year indicates company values has improved, as a result from employee productivity increased and company welfare elevated besides ensuring company sustainability.